Specifics of Forming Schoolchildren's Creative Skills in the Process of Artistic Activity: Assessment of Professional Entrance Examinations Effectiveness - Tatyana V. Pavlenko; Irina Yu. Pushkareva; Anna Schill; Vitaliy S. Elagin; Elena A. Pushkareva (National Research Mordova State University, 2024)
Introduction. The problem of formation of creative person skills in the process of artistic activity is currently topical and thus actively investigated in modern pedagogical science. The relevance of the research is due to the active development of modern rapidly changing reality, contributing to the making of an information technology developing society, which imposes new requirements on the formation of a creative personality. The purpose of the study is to determine the psychological and pedagogical conditions for the formation of creative skills of schoolchildren in the process of artistic activity and to assess the degree of readiness of schoolchildren for creative activity based on results of professional entrance tests. Materials and Methods. The important basis of the ongoing pedagogical research is the methodology of the personal-activity approach, in which creative activity is defined as one of the leading types of activity. This study was conducted from 2021 through 2023 in the logic of pedagogical experiment on the basis of the Childrenʼs Academy of Artistic Creativity and Design. The sample consisted of 155 schoolchildren studying in different areas of artistic and creative activity. Results. The authors show that the processes of education of creative personality are currently undergoing changes in the new conditions of information development and the need to form appropriate thinking. The authors substantiate that it is important to purposefully develop the creative activity of personality and it is necessary to start training from school years. The main and additional psychological and pedagogical conditions of formation schoolchildren creative abilities in the process of artistic activity are defined. The specificity of training of senior schoolchildren in the Children's Academy of Artistic Creativity and Design in special artistic disciplines is shown. The results of evaluation based on the generalization of the data of the professional entrance test in drawing, painting are presented. Discussion and Conclusion. This research contributes to the development of pedagogical knowledge in the field of pedagogical conditions formation for the development of a person's readiness for creative activity. The article will be useful to anyone interested in the study of theoretical and practical aspects of the formation of creative skills of schoolchildren in the process of artistic activity.